(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: The survey aimed to evaluate treatment adherence among people with diabetes with type 2 at the Cardiology – Endocrinology department – At can Tho Hospital. Subjects and research methods: A cross-sectional study was implemented among 283 patients at Can Tho Hospital from March to June 2021 to identify the current situation of patients’ compliance with their treatment regimens and their’ associated factors. Results and discussions: Compliance with food regimen is 60,1%; treatment adherence is 86,6%; physical exercise is 90,8%. Conclusions and recommendations: Therefore, it is necessary to have support methods for patients’ better adherence to treatment, improving their quality of life in the future.